Legitimacy of state power in post-imperial (post-colonial) society: the case of Ukraine - Баталов, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Was investigated the legitimacy of state power in post-imperial (post-colonial) society. Based on the analysis of both Ukrainian and other post-imperial societies was made the conclusion that Ukraine worked its way up similar for most of these cases of taking the foreign set of values, which allowed legitimizing its own state power.